Madu dapat Menurunkan Frekuensi Diare pada Anak: Honey Can Reduce the Frequency of Diarrhea in Children - Siti Nurjanah; Koto, Yeni; Irawan Danismaya (MPI Press, 2022)
Introduction: Diarrhea is the discharge of abnormal and liquid feces. It can also be defined as bowel movements that are abnormal and liquid with more frequency than usual. Objectives: This study aimed to determine the effect of giving honey on diarrhea in children at Rs. Bina Husada Cibinong. Method: This study uses a quantitative approach with the type of experimental research. The design used was quasi-experiment Design with a Non-Equivalent Control Group Pre-test and post-test. The population in this study was all 36 children in the Bina Husada Hospital, Cibinong. In this study, the sample consisted of 20 children who had diarrhea. This research uses a probability sampling technique. The research instrument used was the observation sheet. Data analysis used the Wilcoxon Signed Rank Test. Result: The results showed that the value of the treatment group was -2,919 with a p-value of 0.003 p-value <0.05, and the control group was -2,972 with a p-value of 0.004 <p-value 0.05. Conclusion: There is an effect of giving honey to reduce diarrhea in children.